Living with Huntington's disease : challenges, perspectives and quality of life - Howell, Sherman (Nova Science Publishers, 2020)
Collected papers on specific issues related to the Huntington's disease. Intended for professionals.
Neuroscience research progress
Keywords: poruchy spánku a bdění; Sleep Wake Disorders; Huntingtonova nemoc; klinické zkoušky jako téma; komunikace; emoce; kvalita života; Emotions; Clinical Trials as Topic; genetická terapie; Genetic Therapy; Huntington Disease; Quality of Life; Communication; neurologie